Comparative analysis of surface sanitization protocols on the bacterial community structures in the hospital environment. (August 2022) - Klassert, Tilman E.; Zubiria-Barrera, Cristina; Neubert, Robert; Stock, Magdalena; Schneegans, Antony; López, Mercedes; Driesch, Dominik; Zakonsky, Gregor; Gastmeier, Petra; Slevogt, Hortense; Leistner, Rasmus
Abstract: Objectives: In hospital hygiene, it remains unclear to what extent surface contamination might represent a potential reservoir for nosocomial pathogens. This study investigates the effects of different sanitization strategies on the microbial structures and the ecological balance of the environmental microbiome in the clinical setting. Methods: Three cleaning regimes (disinfectants, detergents, and probiotics) were applied subsequently in nine independent patient rooms at a neurological ward (Charité, Berlin). Weekly sampling procedures included three different environmental sites: floor, door handle, and sink. Characterization of the environmental microbiota and detection of antibiotic resistance genes (ARGs) were performed by 16S rRNA sequencing and multiplex Taq-Man qPCR assays, respectively. Results: Our results showed a displacement of the intrinsic environmental microbiota after probiotic sanitization, which reached statistical significance in the sink samples (median 16S-rRNA copies = 138.3; IQR: 24.38–379.5) when compared to traditional disinfection measures (median 16S rRNA copies = 1343; IQR: 330.9–9479; p < 0.05). This effect was concomitant with a significant increase in the alpha-diversity metrics in both the floor (p < 0.001) and the sink samples (p < 0.01) during the probiotic strategy. We did not observe a sanitization-dependent change in relative pathogen abundance at any tested site, but there was a significant reduction in the total ARG counts in the sink samples during probiotic cleaning (mean ARGs/sample: 0.095 ± 0.067) when compared to the disinfection strategy (mean ARGs/sample: 0.386 ± 0.116; p < 0.01). Discussion: The data presented in this study suggest that probiotic sanitization is an interesting strategy in hospital hygiene management to be further analyzed and validated in randomized clinical studies.